Tumor cell FAP orchestrates EMT and immune suppression in aggressive localized ccRCC - Pellinen, Teijo; Luomala, Lassi; Mattila, Kalle E.; Hemmes, Annabrita; Välimäki, Katja; Arjama, Mariliina; Brück, Oscar; Paavolainen, Lassi; Kankkunen, Elisa; Nisén, Harry; Järvinen, Petrus; Castillon, Leticia; et al. (Ivyspring International Publisher, 2026)
Background: In contrast to most solid tumors, high immune cell infiltration in clear cell renal cell carcinoma (ccRCC) is associated with poor patient prognosis. The biological mechanisms underlying this paradox remain unclear, particularly regarding tumor cell– microenvironment interactions promoting local invasion and recurrence. This study aimed to identify spatially resolved tumor, immune, and stromal features that define aggressive phenotypes in localized ccRCC.
Methods: Multiplex immunofluorescence was performed using a 33-marker panel on 1,728 multi-region tissue cores from 435 surgically treated patients with localized ccRCC. Samples systematically included tumor centers, invasive borders, and adjacent benign tissue. Single-cell analyses quantified immune, stromal, endothelial, and epithelial cell populations within their spatial context.
Results: Spatially resolved profiling uncovered a highly aggressive tumor subtype distinguished by fibroblast activation protein (FAP) expression on tumor epithelial cells, a marker typically associated with stromal cells. Tumor-cell-specific FAP expression characterized an epithelial-to-mesenchymal transition (EMT)-like state and was spatially associated with profound immunosuppression, marked by enrichment of regulatory T cells, exhausted CD8+ T cells, and M2-like macrophages, particularly at the invasive border. Tumor-cell FAP promoted invasion and independently predicted significantly poorer recurrence-free survival (RFS), even in early-stage disease (multivariable Cox p = 0.022 for pT1–2), surpassing established biomarkers such as PD-L1 in capturing aggressive biological features.
Conclusions: Tumor epithelial FAP expression identifies an aggressive, immune-rich subtype of localized ccRCC, integrating EMT with spatially organized immunosuppression. These findings establish tumor-cell FAP as a promising biomarker with substantial translational potential for patient risk stratification, targeted imaging (FAPI-PET), and FAP-directed therapeutic strategies.